IDENTIFIKASI KEBENCANAAN GEOLOGI KABUPATEN CIANJUR, JAWA BARAT - -, Zufialdi Zakaria (Fakultas Teknik Geologi Universitas Padjadjaran, 2008)
Area of Cianjur Regency is represent the part of west Indonesian tectonic. Regional of west Indonesian tectonics is influenced by two plate, that is Indo-Australa and Eurasia, with plate boundary characteristic is Java Trench at south Java. Regional of Cianjur Regency have potency of geological hazard which need to attention from possibility of tsunami in south coast Java, until possibility of volcano eruption (Mt. Gede) in north region. Early warning system is required to various geology disaster referring to various project or activity which have developed or will expand.